Managing distance learning workloads during the MBKM internship program: Challenges and student coping strategies - Syahdan, Syahdan; Firda, Arlian; Herdi, Herdi; Malau, Helmi Lidya (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
The MBKM Internship Program allows students to gain professional experience while simultaneously completing university courses, often requiring them to participate in distance learning. This study investigates the challenges encountered by English Education students at Universitas Lancang Kuning in managing online coursework during their internship activities and explores the strategies they employed to handle academic workloads. Using a qualitative design with thematic analysis, eight students participating in the Certified Internship Program were selected purposively. Data were collected through semi-structured interviews and document analysis. The findings reveal three major challenges in attending distance learning: information gaps caused by limited instructional explanation, communication barriers due to restricted device use during working hours, and schedule conflicts between internship responsibilities and university courses. To address these challenges, students adopted three primary strategies: maintaining peer interaction for academic support, enhancing student–teacher communication through polite and purposeful contact, and maximizing online resources to complete assignments efficiently. The study concludes that although managing both internship duties and online coursework is demanding, students can successfully navigate these dual responsibilities through adaptive communication practices and strategic use of digital resources. These findings highlight the importance of institutional support in synchronizing academic schedules and improving the quality of distance learning for MBKM participants.